YIA 5 Splicing of HDAC7 modulates smooth muscle cell proliferation and neointima formation through nuclear β-catenin translocation. Issue 20 (23rd September 2011) - Zhou, B; Margariti, A; Hu, Y; Xu, Q
Abstract : Vascular smooth muscle cell (SMC) proliferation has an indispensable role in the pathogenesis of vascular disease, but the mechanism is not fully elucidated. The epigenetic enzyme histone deacetylase 7 (HDAC7) is involved in endothelial homeostasis and SMC differentiation but it is unknown whether it could have a role in SMC proliferation. In this study we sought to examine the effect of two HDAC7 isoforms on SMC proliferation and neointima formation. We demonstrated that overexpression of unspliced HDAC7 (HDAC7u) could suppress SMC proliferation through downregulation of cyclin D1 and cell cycle arrest, while spliced HDAC7 (HDAC7s) could not. SiRNA-mediated knockdown of HDAC7 increased SMC proliferation and induced nuclear translocation of β-catenin. Further experiments showed that only HDAC7u could bind to β-catenin and retain it in the cytoplasm. Reporter gene assay and reverse transcription PCR revealed a reduction of β-catenin activity in cells overexpressing HDAC7u, but not HDAC7s. Deletion studies indicated that the C-terminal region of HDAC7u is responsible for the interaction with β-catenin. However, the addition of amino acids to the N-terminus of HDAC7u disrupted the binding, further strengthening our hypothesis that HDAC7s does not interact with β-catenin. The growth factor PDGF-BB increased the splicing of HDAC7 while simultaneously decreasing the expression of HDAC7u. Importantly, in an animal model of femoral artery wire injury, we demonstrated that HDAC7 expression was elevated in a time-dependent manner at both mRNA and protein levels. Knockdown of HDAC7 by siRNA in the injured vessels aggravates neointima formation in comparison with control siRNA. Immunostaining for Ki67 of neointimal lesions displayed that proliferating cells were significantly increased in the vessel wall of HDAC7-siRNA treated group. Thus, our findings demonstrate that splicing of HDAC7 modulates SMC proliferation and neointima formation through β-catenin nuclear translocation, which provides a potential therapeutic target in vascular disease.